STRATEGI SUTRADARA DALAM PENYAMPAIAN BRAND IDENTITY PADA PRODUKSI VIDEO COMPANY PROFILE PT BOOGIE APPAREL INDONESIA - Erika Difa Nadia Kharisma; Rici Tri Harpin Pranata (Jurnal Manajemen Pendidikan, 2026)
Advances in digital communication have encouraged companies to utilize audiovisual media to convey information and strengthen their corporate image. One effective medium is a company profile video, which combines visual, audio, and narrative elements to shape audience perceptions of brand identity PT Boogie Apparel Indonesia has not yet fully optimized company profile videos as a strategic communication tool. Therefore, this study aims to analyze the director’s strategies in directing visual and narrative elements to communicate the company’s brand identity through a company profile video. This study employed a descriptive qualitative method through observation, interviews, active participation, and literature review. The analysis refers to Dancyger’s (2006) “Director’s Idea” approach, which explains the director’s role in pre-production, production, and postproduction stages. The findings reveal that the director implemented strategies through the development of a formal visual concept, directing talents and videographers to create a professional and industrial atmosphere, strengthening narratives focused on company credibility, and conducting screening and evaluation processes. These strategies play an important role in maintaining visual and narrative consistency, thereby reinforcing audience trust and strengthening the brand identity of PT Boogie Apparel Indonesia.